Effects of post‐glacial phylogeny and genetic diversity on the growth variability and climate sensitivity of European silver fir. (17th March 2016) - Bosela, Michal; Popa, Ionel; Gömöry, Dušan; Longauer, Roman; Tobin, Brian; Kyncl, Josef; Kyncl, Tomas; Nechita, Constantin; Petráš, Rudolf; Sidor, Cristian Gheorghe; Šebeň, Vladimír; Büntgen, Ulf
Summary: Growth rates of European silver fir ( Abies alba Mill.) rapidly increased in the last century. At the same time, ring widths declined at the species southern distribution limits in the Mediterranean. Such diverse growth trends and responses have largely been attributed to regional climate conditions, but this was prior to considering the species' post‐glacial phylogeny. A dendrochronological network composed of 1961 tree‐ring width series (TRW) from 78 silver fir sites between 365 and 1400 m a.s.l. along the Carpathian Arc was compiled. Spatial differences in the species' genetic diversity were investigated from genetic data of 69 silver fir populations in the region. Differences in growth variability and climate sensitivity were then related to post‐glacial phylogeny and genetic diversity. Significant differences in interannual and longer‐term growth trends and climate responses across the Carpathian Arc were found to coincide with the geographical north–south separation of two post‐glacial populations from effective refugia originating from the Apennine and Balkan peninsulas. Summer temperature was the main driver of growth in the western (Apennine) lineage, whereas ring widths in the Balkan population from the east were predominantly controlled by summer drought. Fir specimens that originated from the Balkan lineage exhibited higher genetic diversity and more regular growth dynamics and also appeared to be less sensitive to air pollution during the 1970s. Synthesis . Although the phylogeny of forest trees has largely been neglected in most dendroecological studies, results here indicate the importance of different post‐glacial histories for the growth sensitivity and adaptability to varying environmental factors. Decision‐making under future climate warming scenarios (for building resilience through forest management) should therefore consider different phylogenetic origins. Abstract : Phylogenetic origin of Abies alba might have affected the species' growth in Europe. Using a large dendrochronological and genetic data spanning across the Carpathian Mountains, where the two main post‐glacial lineages met (the white path), we revealed the distinct growth and climate sensitivity between the two populations. These findings indicate the importance of different post‐glacial histories for the growth sensitivity and adaptability to varying environmental factors.